The Early and Middle Bronze Age Textile Tools from the Aeolian Islands (Italy) - Katarzyna Żebrowska (Fasciculi Archaeologiae Historicae)
The Aeolian ceramic textile tools dated to the advanced Early and Middle Bronze Age (c. 1600-1250 BC) comprise the only evidence for textile manufacture and are a unique source of information about the technology of textile production used in the Early-Middle Bronze Age (EBA-MBA) in the Aeolian Archipelago (province of Messina, Italy). A recent re-examination of 76 out of over 140 of these tools has shown that heavier spindle whorls (71-153 g) dominate in the more numerous MBA material. The high weight values of the Aeolian spindle whorls, uncommon in the area and epoch, could point to the prevalent use of long staple animal fibres, e.g. wool, which requires heavier implements in order to be spun, in yarn manufacture in the archipelago. A group of very heavy tools (165-199/222 g), difficult to classify, has been identified in the MBA material as well. It is suggested that these particular implements were potential heavy spindle whorls used primarily for spinning long hard plant fibres, such as flax, and plying yarns or producing twines.